ANALYSIS OF WORK MOTIVATION AND TEACHER TRAINING EFFECT ON TEACHERS PERFORMANCE MODERATED BY PRINCIPAL LEADERSHIP IN SENIOR HIGH SCHOLL AT DISTRICT KAYEN OF PATI REGENCY - Rudi Hartono, 12.52.02.0200; Srimindarti, Ceacilia (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to determine the influence of work motivation and training of teachers on teacher performance moderated by principal leadership in senior high school at district Kayen of Pati regency. This study used a high school teacher population in the district Kayen of Pati regency by 123 teachers. The analysis technique used is the quasi moderation models with interaction techniques. The results showed that work motivation has a positive and significant impact on teachers performance, teacher training has a positive and significant impact on teachers performance, school leadership has significant positive effect on teachers performance, school leadership weaken the influence of work motivation on teachers performance, but leadership schools are not able to moderate the influence of teacher training on teachers performance. Keywords: work motivation, teacher training, principal leadership, teacher performance.